Belgium : Staff Report for the 2004 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2005)
This 2004 Article IV Consultation highlights that during the recent upswing, growth in Belgium has been comparatively robust, propelled by strong household spending and supported by the global recovery as well as macroeconomic policies. Tax cuts and wage increases have sustained disposable income growth, while household savings resumed a declining trend amid improvements in the economic outlook and public finances. In the IMF staff's view, economic growth is expected to continue at a healthy pace in 2005, driven by private consumption as well as a likely strengthening of corporate investment and employment growth.